Case formulation in emotion-focused therapy. (3rd April 2017) - Goldman, Rhonda N.
ABSTRACT: Case formulation in EFT is a relatively new concept and useful tool that helps therapists to both conceptualize cases as well as follow markers across therapy in order to initiate tasks that promote change in emotional processing. The paper summarizes the emotion-focused approach to case formulation and illustrates it in appellation to a case. First, the guiding principles of case formulation are explicated. Next, the three stages, unfolding the narrative and observing emotional processing style, cocreating a focus and identifying the core emotion, and process formulation, are outlined. The 14 steps of case formulation are nested within the 3 stages. Each of the steps is specified in application to the case of Sophie.